Dietary Administration of the Bacillus subtilis Enhances Immune Responses and Disease Resistance in Chickens - Guo, Mengjiao; Li, Mingtao; Zhang, Chengcheng; Zhang, Xiaorong; Wu, Yantao (Frontiers in Microbiology, 2020)
Bacillus subtilis (B. subtilis) has a variety of proposed beneficial effects for chickens, including growth promotion and disease prevention. In this study, chickens were fed a diet containing B. subtilis for 21 days and growth performance, intestinal morphology, intestinal microbiota, immune responses, and disease resistance were investigated. After 21 days of feeding, chickens fed a diet containing B. subtilis had higher body weights. The concentrations of serum immunoglobulins IgA and IgM were significantly increased by B. subtilis in the diet. Moreover, chickens fed with B. subtilis had greater villus height (VH), shallower crypt depth (CD), and a higher VH/CD ratio in the jejunum than chickens fed a standard control diet. Diet with B. subtilis can balance intestinal microbiota, facilitate an increase in beneficial bacteria, and inhibit the pathogenic bacteria after 21 days of feeding. After an Escherichia coli (E. coli) challenge, the survival rate of chickens fed with B. subtilis was 66.67%, which was significantly higher than the controls. The E. coli contents in spleens and lungs from chickens fed a diet with B. subtilis were lower than those in controls. In addition, B. subtilis can trigger the toll-like receptor 4 and cause induction of proinflammatory cytokine (Il1β, Il6, and Il8) production to develop innate immune responses in chickens. In conclusion, diets containing B. subtilis can improve growth performance, serum immunoglobulin levels, the intestinal villus-crypt system, intestinal homeostasis, immune responses, and disease resistance against E. coli in chickens.